Enhanced Electrochemical Performance of Li‐ and Mn‐Rich Cathode Materials by Particle Blending and Surface Coating. Issue 10 (11th March 2020) - Li, Zhao; Li, Qiang; Wu, Shuaijin; Zhang, Anbang; Zhuo, Haoxiang; Zhang, Gangning; Wang, Zhong; Wang, Lin; Ren, Zhimin; Wang, Jiantao
Abstract: A Li‐ and Mn‐rich material Li1.18 Mn0.55 Ni0.18 Co0.09 O2 (LMR) exhibits a high specific capacity; however, this material has serious problems, including a poor rate capability and limited cycling life. A jet crushing method is used to break micron‐sized LMR particles synthesized by a solid‐state reaction into nano‐sized particles. Compared to micron‐sized particles, nano‐sized LMR particles possess a higher rate capability due to shorter Li + diffusion pathway, but also an increase in side reactions with the electrolyte leads to poorer cycling performance. Herein, we propose a material engineering strategy that combines micron‐ and nano‐sized particle blending and a cerium oxide (CeO2 ) surface coating modifications to enhance the electrochemical performance of LMR material. X‐ray diffraction (XRD) patterns and transmission electron microscopy (TEM) images demonstrate that the cubic structure of CeO2 is uniformly distributed on the surface of LMR, which is supposed to suppress the electrode/electrolyte side reactions by preventing electrode particles from being directly exposed to the electrolyte. As a result, the discharge capacity of the modified LMR material is 153.1 mAh g −1 at 5 C compared to 139.1 mAh g −1 with the pristine material. The capacity retention of the modified material is 82.8 % after 200 cycles at 1 C, which is higher than the 77.1 % capacity retention of the pristine material. X‐ray photoelectron spectroscopy (XPS) reveals that the CeO2 coating layer has a significant role in mitigating oxygen release from the surface of the LMR material during cycling. Abstract : Combination strategy: A practical engineering strategy that combines particle blending and surface coating modifications was proposed to enhance the electrochemical performance of Li‐ and Mn‐rich material Li1.18 Mn0.55 Ni0.18 Co0.09 O2 (LMR). Nano‐sized particles are obtained by a jet crushing method and then blended with micron‐sized particles, which contributes to tap density and high rate capability of LMR. The CeO2 coating further improve cyclic performance of LMR by suppressing electrode/electrolyte side reactions.